Pengembangan Booklet Budidaya Jamur Edible Sebagai Bahan Ajar Mikologi: (Development of Edible Mushroom Cultivation Booklet as Mycology Teaching Materials) - Harlis Harlis; Retni S. Budiarti; Desfaur Natalia (BIODIK, 2021)
This study aims to develop an edible mushroom cultivation booklet in the mycology course. The method used in this research is research and development using the ADDIE model. This research was conducted with the stages of analysis, design, development, implementation, and evaluation. Based on the results of the study, it shows that the feasibility of the booklet used is declared feasible according to the results of media validation and material validation by the validator team. On the results of the first media validation with a score of 75% "good" and the second media validation is 90% "very good". While the results of the validation of the first material with a score of 70 "good" and the result of the second validation is 90 "very good". After the assessment was carried out by the validator team, then the booklet was tested with small groups and large groups of biology education students. Based on the results of the small group student response test, it was found that 91.5% was included in the "very good" category, and the results of the large group student responses obtained a percentage of 98.3% included in the "very good" category. The results showed that the edible mushroom cultivation booklet developed was suitable for use as a learning resource, able to foster interest and entrepreneurial spirit for Biology Education Students of Jambi University. Abstrak. Penelitian ini bertujuan mengembangkan booklet budidaya jamur edible pada mata kuliah mikologi. Metode yang digunakan pada penelitian ini yaitu penelitian dan pengembangan dengan menggunakan model ADDIE. Penelitian ini dilakukan dengan tahap analysis, design, development, implementation, dan evaluation. Berdasarkan hasil penelitian menunjukkan bahwa kelayakan terhadap booklet yang digunakan dinyatakan layak sesuai hasil dari validasi media dan validasi materi oleh tim validator. Pada hasil validasi media ke-1 dengan skor 75% â€œbaikâ€ dan validasi media yang ke-2 yaitu 90% â€œsangat baikâ€. Sedangkan hasil validasi materi yang ke-1 dengan skor 70 â€œbaikâ€ dan hasil validasi yang ke-2 yaitu 90 â€œsangat baikâ€. Setelah dilakukan penilaian oleh tim validator selanjutnya booklet dilakukan ujicoba dengan kelompok kecil dan kelompok besar terhadap mahasiswa pendidikan biologi. Berdasarkan hasil dari uji respon mahasiswa kelompok kecil diperoleh persentase 91,5% termasuk dalam kategori â€œsangat baikâ€, dan hasil respon siswa kelompok besar diperoleh persentase 98,3% yang termasuk dalam kategori â€œsangat baikâ€. Hasil penelitian menunjukkan bahwa booklet budidaya jamur edible yang dikembangkan layak digunakan sebagai sumber belajar, mampu menumbuhkan minat dan jiwa entreprenership bagi Mahasiswa Pendidikan Biologi Universitas Jambi.